Tuberculosis in North-East India: patient profile and treatment outcome of patient attending RNTCP - Kayina, T. Kayia Priscilla; Tarao, M. Shyami; Nula, Polly (International Journal Of Community Medicine And Public Health, 2019)
Background: Tuberculosis is a disease of global concern. India with its high burden of Tuberculosis, HIV and HIV-TB co-infection, this disease continue to have tremendous impact on its denizens especially the north-eastern states of the country because of its problem of HIV. It is imperative to understand every aspects of the disease for effective prevention and control. Methods: A retrospective record study of tuberculosis units was conducted. Results: The proportion of males was more as compared to females, with more cases seen with increasing age. Pulmonary TB was seen more among males, whereas extra-pulmonary TB was seen more among females. Favorable treatment outcome was seen in 84.7% of the population. HIV-TB Co-infection was seen 6.5% of the patients, with 46.3% having extra-pulmonary TB. Favorable treatment outcome was seen among them too. Conclusions: More common in males, showing increasing number of patients in older age group with favourable outcomes on treatment in all categories including HIV-TB co-infection patients.